Iron in ventricular remodeling and aneurysms post-myocardial infarction - Wang Zuoyan; Ding Xiang; Pan Jingyu; Wang Xueyan; Lin Jieming; Wang Xinzhu (Open Medicine)
Post-myocardial infarction (MI) complications, including ventricular remodeling (VR) and left ventricular aneurysm (LVA) formation, significantly affect patient prognosis and quality of life. Both iron overload and deficiency play critical roles in these pathological processes.